Sequential treatment with ursolic acid chlorophenyl triazole followed by 5-fluorouracil shows synergistic activity in small cell lung cancer cells - Zhu, Rui-Xia; Zhao, Lei; Zhang, Yu-Kun; Luo, Peng; Liu, Si-Hai; Wang, Jin-Guang (Bangladesh Journal of Pharmacology, 2015)
Combination therapy has prolonged the survival of patients with small cell lung cancer (SCLC), an aggressive neoplasm characterized by a high rate of metastasis. In the present study the effect of sequential treatment of ursolic acid chlorophenyl triazole (UACT) followed by 5-fluorouracil (5-FU) on human small cell lung cancer cells was investigated. The results revealed a synergistic effect of the sequential treatment with UACT and 5-FUcombination on cytotoxic activities, NF-kB protein activation, repression of TNF-induced NF-kB-dependent reporter gene expression, and TNF-induced COX-2, MMP-9 and Cyclin D1 activation in H209 cells. The synergism in apoptotic cell death was observed in H209, H69, 87-5,and Lu135 cells. The synergistic effect of UACT and 5-FU was observed at a concentration of 50 nM of UACT and 20 µM of 5-FU. These results indicate that UACT and 5-FU combination can be a promising chemotherapeutic regimen in the treatment of SCLC.